Adaptation of David Kolb's inventory of learning styles in Peruvian students - Barboza Zelada, Luis Alberto (2019)
The David Kolb Learning Styles Inventory was adapted for a population of 699 students, 382 men and 317 women in the 1st and 2nd years of secondary school in the military promoters of Metropolitan Lima. It is assumed as a theoretical basis that Kolb's learning styles refer to the way each person approaches learning in a peculiar way; fruit of inheritance, previous experiences and current demands of the environment in which it operates. Obtaining evidence of content validitythrough the Judges Criterion, using the Aiken reliability index V; For the Internal Consistency the Cronbach's Alpha Coefficient was used, obtaining a score of 0.99 and establishing the Percentiles by Areas EC - OR - CA - EA and by Dimensions CA - EC (x) and EO - OR (y), determining the categories based on the established coordinates, whose ranges are x = -21 to 11 and = -17 to 14.